SOME BIOLOGICAL FEATURES AND HARM OF THE PEA BEETLE (BRUCHAS PISORUM S.) IN THE CONDITIONS OF THE FERGANA VALLEY. (Scientific journal of the Fergana State University, 2024)
The article presents an analysis of scientific works on the pest of pea plants grown in the Fergana Valley. As a result of the observations, it can be noted that the pea plant is damaged by the pea beetle - Bruchus pisorum L. Because among pests of leguminous crops this is one of the most common types of pests. Beetle larvae are univoltine larvae that feed only on pea plants. A common feature of beetles is their sensitivity to external air temperature, including at high air temperatures the beetles are active, and at low air temperatures they hide among flowers or young leaves.General entomological rules were used in the work. When analyzing, a distinctive feature of beetles from other species can be distinguished by the fact that their hard wings do not cover the body from the top to the end. In addition, the white border on the body of the beetle clearly distinguishes the species from other granivores. Like all pest beetles, these beetles do little damage to the plant during the ripening period. Pests are transmitted in the larval stage. If a plant produces pods for a long time on fertile soil, pests develop that damage the milk pods over a long period of time. Therefore, such peas retain their germination capacity. Insect larvae also develop according to age, with changes in body color. Over time, invisible spots in the form of black dots form on damaged pods. Damaged pods become contaminated with larval excrement, resulting in low-quality products unsuitable for human consumption.